A Compact Three-Dimensional Two-Layer Flexible Hinge - Nicolae Lobontiu; Morgan Moses; Jozef Hunter; Daniel Min; Mircea Gh. Munteanu (Machines, 2023)
The paper proposes a new three-dimensional flexible hinge formed of several serially linked straight- and circular-axis segments that are disposed of in two layers. The novel hinge configuration is capable of large displacements and can be implemented in precision-compliant mechanisms that need to cover large spatial workspaces. Based on simplified geometry, an analytical compliance model is formulated that connects the loads to the displacements at one end of the hinge. Finite element simulation and experimental prototype testing of actual-geometry hinge configurations confirm the analytical model predictions. A related compliance-based analytical model evaluates the maximum loads that can be applied to the hinge and the resulting displacements. The two small-deformation analytical models are subsequently utilized to investigate the relationship between geometric parameters and the hinge performance qualifiers.